Prevalence and Pattern of Hospital Acquired Infection in Surgery Ward, Dhaka City (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Hospital acquired infection among the patients of post-surgery is a global issue linked to extra burden on individual health, health sector and overall economy of the country. Prevention is the utmost important intervention to overcome this issue.Objective: To investigate the prevalence and pattern of Hospital acquired infection among the post-surgical patients in Dhaka city.Methods: This is the cross-sectional study conducted in Shaheed Suhrawardy Medical college hospital (Oral and Maxillofacial surgery ward) and Dhaka Medical college Hospital (General surgery and Gynae ward). The cross- sectional design observed 180 participants who undergo surgery and fulfilled specific inclusion criteria. Convenience sampling, a non-probability sampling technique, was used for participant selection. Data were collected by face-to-face history taking and considering history sheets with a semi- structured questionnaire.Results: Among 180 hospital admitted patients, a significant frequency of patients developed HAI 57.78% and in 42.22% did not develop HAI. The Male patients was 30% and female 70%. The Male patients who developed HAI were 8.89%, Female 48.89%. where 20% reported consuming smoked tobacco, 33.33% smokeless tobacco and 46.67% consumed no tobacco. So, a total of 53.33% of the population used tobacco. The study identified a significant association (p